Passages That Require Agility in the Cello Parts of Tchaikovsky’s Manfred and Symphony No. 4 - Ayşem Ersoy (Konservatoryum)
This paper presents suggestions and exercises to solve the problems related to agility and articulation due to the anatomy of the left hand while performing the cello parts of Tchaikovsky’s Manfred Symphony and Symphony No. 4. The cognitive methods in instrument training are explored in this study. These cognitive methods are studies aimed at restructuring the unintentionally developed negative thought systems. A certain experience is consciously visualized in the brain using mental imagery. In this context, the importance of imagery and behavioral methods in performance is presented. This study examined various physical therapy techniques applied by musicians, including the Alexander technique and the Feldenkrais method— two of the most well-known methods. The discussion also focuses on methods such as yoga andmeditation that are used for mental and physical preparation in addition to left-hand anatomy, left-hand pattern, articulation, and agility. Finally, the paper provides exercise examples on the correct use of fingering and position transitions for the fast passages of the cello parts in Manfred and Symphony No. 4 in performance practices.